Evaluating the effects of uncertainty on projections of greenhouse gas emissions : a biofuel case study in Brazil - Barroso, Renan Maron (2019)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies